2021
DOI: 10.1136/bmjopen-2020-046453
|View full text |Cite
|
Sign up to set email alerts
|

Is health literacy associated with antibiotic use, knowledge and awareness of antimicrobial resistance among non-medical university students in Egypt? A cross-sectional study

Abstract: ObjectivesAntibiotic resistance is a global public health concern, especially in developing countries, where antibiotic misuse is widespread. However, studies investigating relevant factors, particularly in youth, are limited. This study examined the levels of health literacy (HL) and their association with antibiotic use, knowledge of antibiotics and awareness of antibiotic resistance among university students in Egypt.DesignA cross-sectional study was conducted using self-administered questionnaires during 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 25 publications
(48 reference statements)
6
22
1
1
Order By: Relevance
“…However, there was some confusion regarding some items, such as “Farmers should give fewer antibiotics to food-producing animals” and “People should not keep antibiotics and use them later for other illnesses”, which were the least agreed upon by the participants to address the problem of antibiotic resistance. Previous research yielded similar results [ 2 , 20 ]. The findings of this study propose instant solutions and various techniques to improve antibiotic stewardship in various livestock sectors.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…However, there was some confusion regarding some items, such as “Farmers should give fewer antibiotics to food-producing animals” and “People should not keep antibiotics and use them later for other illnesses”, which were the least agreed upon by the participants to address the problem of antibiotic resistance. Previous research yielded similar results [ 2 , 20 ]. The findings of this study propose instant solutions and various techniques to improve antibiotic stewardship in various livestock sectors.…”
Section: Discussionsupporting
confidence: 83%
“…Acquainting patients with the fact that antibiotic resistance is attributed to bacteria’s capacity to overcome the action of therapeutic agents and that it is a global issue making everyone susceptible to antibiotic-resistant, difficult-to-treat infections may enhance social contributions to the implementation of antibiotic resistance prevention strategies. Previous studies reported similar results [ 2 , 20 , 36 ]. The findings of this study revealed that more than four-fifths (83%) of the participants made wrong assumptions regarding whether antibiotics heal sore throats, whereas less than half (43%) were incorrect in their assertion that antibiotics can be used to treat colds and the flu.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Perilaku penggunaan antibiotika yang tepat salah satunya berdasarkan resep dokter juga sejalan dengan penelitian yang dilakukan di Kolkata, India 16 , pada mahasiswa sarjana kedokteran dimana menyimpulkan bahwa mayoritas (75,5%) partisipannya menggunakan antibiotika melalui resep dokter dan 54% menjalani pengobatan sampai selesai. Berdasarkan hasil tersebut dapat dipahami bahwa penggunaan antibiotika yang tinggi tersebut diimbangi dengan tingkat pengetahuan yang tinggi pula, sehingga para partisipan mengerti apa yang dilakukannya dengan konsultasi kepada dokter terlebih dahulu 17,18 . Namun, berbeda dengan penelitian serupa yang dilakukan pada mahasiswa Universitas di Malaysia yang mana hanya 25,7% dari 424 partisipannya mengaku menggunakan antibiotika pada bulan-bulan sebelumnya 19 .…”
Section: Gambar 1 Hasil Perilaku Penggunaan Antibiotikaunclassified